2015
DOI: 10.1111/joca.12092
|View full text |Cite
|
Sign up to set email alerts
|

Can't Buy Me Green? A Review of Consumer Perceptions of and Behavior Toward the Price of Organic Food

Abstract: Support for organic farming is a promising policy for improving sustainability in the food sector. Further consumer demand, however, is hindered by high prices. We review research from 2000 to 2014 on the role of perceived price, income, price knowledge, willingness to pay, and reactions to price changes on organic food. We find that price is the major perceived barrier to purchase. Income is only a partial explanatory factor and is superseded by psychographic variables. Willingness to pay a premium is around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
205
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 336 publications
(219 citation statements)
references
References 125 publications
(246 reference statements)
11
205
1
2
Order By: Relevance
“…Although organic farming systems yield less food, recently estimated to be ∼19%, the gap can be reduced or even abolished with further research and development work, as indicated in recent publications (90,92). Export/import and transport may also be important for sustainability (5). Organic vegetables, fruits, and herbs grown in low-income countries, particularly in Africa, are produced almost exclusively for the export market.…”
Section: Factors Driving Organic Food Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although organic farming systems yield less food, recently estimated to be ∼19%, the gap can be reduced or even abolished with further research and development work, as indicated in recent publications (90,92). Export/import and transport may also be important for sustainability (5). Organic vegetables, fruits, and herbs grown in low-income countries, particularly in Africa, are produced almost exclusively for the export market.…”
Section: Factors Driving Organic Food Consumptionmentioning
confidence: 99%
“…Consumers are prepared to pay more for products that involve less processing and that are grown free of pesticides and genetically modified organisms, perhaps by local farmers considered worthy of support (8,48,70). Insufficient availability, convenience concerns, and high prices for organic food are identified as factors that limit the consumption of organic food (5,31,48,63).…”
Section: Factors Driving Organic Food Consumptionmentioning
confidence: 99%
“…Actually it is not possible to define precisely all the dimensions related to this offer. Scholars are still working to provide valid information on strategic aspects such as the market segmentation (Hansen et al, 2018;Peštek et al, 2018;Sultan et al, 2018), the role of awareness (Asif et al, 2018), the willingness to pay higher prices (Aschemann-Witzel, and Zielke, 2017), the country of origin (Thøgersen et al, 2017), the relationship with health concern (Apaolaza et al, 2018) or the perspectives on production (Popović et al, 2018). Analyzing the evidences from the market, increasing sales are registered.…”
Section: The Eco-label Frameworkmentioning
confidence: 99%
“…The impact of COO on consumer choices is one of the oldest and most extensively researched topics in global marketing and consumer behaviour, and a wide range of contingencies and moderators of COO effects has been identified (Pharr, 2005, Verlegh andSteenkamp, 1999). The key role of consumer demand for the development of the organic market has also given rise to a growing literature (Aschemann-Witzel and Zielke, 2015, Hemmerling et al, 2015, Hughner et al, 2007, Rödiger and Hamm, 2015. Although there are many studies of consumer preferences for COO on the one hand and organic food on the other, research on COO effects in the context of organic food is scarce (Xie et al, 2015).…”
Section: Introductionmentioning
confidence: 99%